2005
DOI: 10.1002/ijc.20740
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and prognosis for head and neck cancer in the United States: A site‐specific analysis of the SEER database

Abstract: Despite recent advances in the diagnosis and treatment of head and neck cancer, there has been little evidence of improvement in 5-year survival rates over the last few decades. To determine more accurate trends in site-specific outcomes as opposed to a more general overview of head and neck cancer patients, we analyzed the site-specific data collected in the Surveillance, Epidemiology, Population-based cancer statistics in the United States (US) for 2004 is expected to yield 28,260 new cases of oral cavity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
640
5
27

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 748 publications
(697 citation statements)
references
References 21 publications
25
640
5
27
Order By: Relevance
“…In the last 30 years, progress in the treatment of head and neck cancer has improved the quality of life of patients via the use of innovative surgical and endoscopic techniques that are aimed at the preservation of organ function, mainly in laryngeal tumors (Allegra et al, 2012). The 5-year survival rate for these patients has remained in the range 50-60% for the last three decades (Carvalho et al, 2005). The main causes of death remain the recurrence of locoregional disease that is unresponsive to conventional treatments and distant metastases (Allegra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the last 30 years, progress in the treatment of head and neck cancer has improved the quality of life of patients via the use of innovative surgical and endoscopic techniques that are aimed at the preservation of organ function, mainly in laryngeal tumors (Allegra et al, 2012). The 5-year survival rate for these patients has remained in the range 50-60% for the last three decades (Carvalho et al, 2005). The main causes of death remain the recurrence of locoregional disease that is unresponsive to conventional treatments and distant metastases (Allegra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even though some diseases have undergone a therapeutic revolution, such as pediatric leukemia and some lymphomas, the treatment of others has improved only slightly. For example, the stage-adjusted 5-year survival of patients with head and neck cancer has remained essentially unchanged for well over 30 years ( 1 ). Clearly, one of the most urgent challenges is to translate findings in basic biology into applicable strategies for patient care.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the death rate per 100,000 population for laryngeal versus oral/oropharyngeal carcinomas was 2.36 versus 4.06, respectively [2]. An analysis of the Surveillance, Epidemiology, and End-Results (SEER) data for HNSCC demonstrates that this is not due to clinical stage at presentation [3]. Analysis of the SEER registry data demonstrated that site-specific survival differences remain across stages; defined as local, regional, and distant.…”
Section: Introductionmentioning
confidence: 99%
“…This site-specific difference may also be seen in the varied treatment approaches. While surgery and radiation therapy were once the only primary treatments offered, head and neck sites such as the larynx and oropharynx have seen a paradigm shift to chemotherapy and radiotherapy [4], while oral cavity tumors are still treated predominantly with surgery [3]. There is also a stage related difference in therapy, with early stage lesions often managed with single modality treatment and advanced stage disease treated with multimodality therapy.…”
Section: Introductionmentioning
confidence: 99%